1998
DOI: 10.1021/es980019q
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organic Films on the Hygroscopicity of Ultrafine Sulfuric Acid Aerosol

Abstract: In ambient air, organic chemicals are common constituents of aerosol particles, and many of them are surfaceactive. If these compounds are present as surface films on aqueous droplets, mass transfer of gaseous molecules into or out of the droplets could be impeded, and the hygroscopic growth of acidic droplets could be reduced. In this work, the effects of organic films on the hygroscopic growth rate of ultrafine H 2 SO 4 aerosols (40-120 nm) were investigated under relative humidity conditions of 20-85% and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 25 publications
1
80
1
Order By: Relevance
“…In general, our results with the rather little soluble O 3 are in line with previous studies. Xiong et al (1998) showed that a C 18 coating reduced the hydroscopic growth rate of sulphuric acid aerosol, while a coating of oleic acid (nonlinear and unsaturated) had no effect, likely related to the fact that oleic acid does not form condensed liquid films at pressures, where the saturated straight chain C 18 fatty acid does (Seidl, 2000). Similarly, related the permeability of monolayers to the molecular properties and pressure-area isotherms and demonstrated that the uptake of acetic acid through monolayers of saturated C 18 and C 30 alcohols into an aqueous phase was strongly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In general, our results with the rather little soluble O 3 are in line with previous studies. Xiong et al (1998) showed that a C 18 coating reduced the hydroscopic growth rate of sulphuric acid aerosol, while a coating of oleic acid (nonlinear and unsaturated) had no effect, likely related to the fact that oleic acid does not form condensed liquid films at pressures, where the saturated straight chain C 18 fatty acid does (Seidl, 2000). Similarly, related the permeability of monolayers to the molecular properties and pressure-area isotherms and demonstrated that the uptake of acetic acid through monolayers of saturated C 18 and C 30 alcohols into an aqueous phase was strongly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Sjogren et al (2004) found that (NH 4 ) 2 SO 4 -adipic acid particles (50 wt% and 76wt% adipic acid) exhibited a lower G f at a residence time of less than 4 s than the G f at more than 4 s at 78-91%RH after deliquescence. Xiong et al (1998) found that submicrometer sulfuric acid (H 2 SO 4 ) particles attained their equilibrium size within 6 s. On the other hand, the G f of H 2 SO 4 particles coated with three monolayers of lauric acid further increased as the residence time increased from 6 s to 10 s, providing evidence that the coated H 2 SO 4 particles had not yet reached their equilibrium size within 6 s. Organic films can act a physical barrier to retard the water condensation (or evaporation) rate in planar solutions and on particle surfaces (Gill et al, 1983;Barnes, 1986) and can lower the accommodation coefficient (Pandis et al, 1995). A summary of laboratory studies on the evaporation and condensation rates of water vapor from particles in the presence of organic films has been presented by Chuang (2003).…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…McMurry and Stolzenburg (1989) pointed out that the effects of organic coatings or surfactants in atmospheric particles on the equilibrium time are unknown. It is possible that an organic coating or surface-active compounds can hinder the transport of water across the particle/air interface and result in non-equilibrium growth measurements in field studies using a TDMA (Xiong et al, 1998).…”
Section: Field Measurementsmentioning
confidence: 99%
“…This does not necessarily rule out similarities: salt particles in Helsinki might be coated with, e.g. hydrocarbons from traffic and other combustion processes that affect their water solubility (Hansson et al, 1998;Xiong et al, 1998). Another potential explanation is that the higher growth mode in Helsinki results from ageing: originally less-hygroscopic particles tend to gain soluble properties when aged (e.g.…”
Section: Frequency Of Occurrencementioning
confidence: 99%